Cancer risk in socially marginalised women: An exploratory study. (January 2019) - Hanson, Sarah; Gilbert, Duncan; Landy, Rebecca; Okoli, Grace; Guell, Cornelia
Abstract: Background: Cancer is a leading cause of premature death in women worldwide, and is associated with socio-economic disadvantage. Yet many interventions designed to reduce risk and improve health fail to reach the most marginalised with the greatest needs. Our study focused on socially marginalised women at two women's centres that provide support and training to women in the judicial system or who have experienced domestic abuse. Methods: This qualitative study was framed within a sociological rather than behavioural perspective involving thirty participants in individual interviews and focus groups. It sought to understand perceptions of, and vulnerability to, cancer; decision making (including screening); cancer symptom awareness; and views on health promoting activities within the context of the women's social circumstances. Findings: Women's experiences of social adversity profoundly shaped their practices, aspirations and attitudes towards risk, health and healthcare. We found that behaviours such as unhealthy eating and smoking need to be understood in the context of inherently risky lives. They were a coping mechanism whilst living in extreme adverse circumstances, navigating complex everyday lives and structural failings. Long term experiences of neglect, harm and violence, often by people they should be able to trust, led to low self-esteem and influenced their perceptions of risk and self-care. This was reinforced by negative experiences of navigating state services and a lack of control and agency over their own lives. Conclusion: Women in this study were at high risk of cancer, but it would be better to understand these risk factors as markers of distress and duress. Without appreciating the wider determinants of health and systemic disadvantage of marginalised groups, and addressing these with a structural rather than an individual response, we risk increasing cancer inequities by failing those who are in the greatest need. Highlights: Marginalised women were at very high risk of cancer and late presentation. Lifelong adversity shaped practices, health aspirations and attitudes to risk. Risk factors presented as coping mechanisms and markers of distress and poverty. Structural failings, distrust and lack of control shaped trust in health systems. A response is needed that addresses structural failings and systemic disadvantage.